National survey of the injury prevention activities of children's centres - Watson, M.C.; Mulvaney, Caroline A.; Kendrick, Denise; Stewart, Jane; Coupland, Carol; Hayes, Mike; Wynn, Persephone (Wiley, 2014)
Children's centres were established across England to provide a range of services including early education, social care and health to pre-school children and their families. We surveyed children's centres to ascertain the activities they were undertaking to prevent unintentional injuries in the under fives. A postal questionnaire was sent to a sample of children's centre managers (n = 694). It included questions on current activities, knowledge and attitudes to injury prevention, health priorities and partnership working. Responses were received from 384 (56%) children's centres. Overall, 58% considered unintentional injury prevention to be one of the three main child health priorities for their centre. Over half the respondents (59%) did not know if there was an injury prevention group in their area, and 21% did not know if there was a home safety equipment scheme. Knowledge of how child injury deaths occur in the home was poor. Only 11% knew the major cause of injury deaths in children under five. Lack of both staff time and funding were seen as important barriers by children's centre staff to undertake injury prevention activities. Nearly all stated that training (97%) and assistance with planning injury prevention (94%) would be helpful to their centres. Children's centres need further support if they are to effectively tackle this important public health area.